Low Cost and Easy to Implement Physical and Hydrological Soil Assessment of Shade-Grown Coffee in Santa Rosa, Guatemala - Marcelo Daniel Gerlach; Sergio Esteban Lozano-Baez; Mirko Castellini; Nery Guzman; Wilmer Andrés Gomez; Bayron Medina (Land, 2023)
Coffee agroecosystems are considered to have the potential to impact soil hydrological functions positively, such as water infiltration and soil moisture retention; however, it is not clear how hydrodynamic soil properties regenerate after land-use change and what easy to implement and low-cost indicators there are. Common methodologies to assess soil hydraulic properties are time consuming and expensive. Therefore, the development of easy, robust, and inexpensive methodologies is one of the main steps in achieving a comprehensive understanding of the effects of land-use change on soil hydraulic and physical characteristics in time and space. In order to assess soil properties, we investigated the saturated hydraulic conductivity (Ks), and two micro-climatic indicators: soil volumetric water content (VWC) and temperature above (TAL) and below soil cover (TBL) in four land-use types: a thirty-year-old shade-grown coffee (CN); a seven-year-old shade-grown coffee (CP); a one-year-old shade-grown coffee (CC) as well as a non-commercial pasture (PR), in the municipality of Nueva Santa Rosa, Santa Rosa department, Guatemala. Additionally, we conducted a visual soil assessment (VSA) elaborated on by the Catholic Relief Services for coffee soils in Central America. We used the steady version of the simplified method based on a Beerkan Infiltration run (SSBI method) to obtain Ks values after determining historical land use. The SSBI methodology is thought to be a suitable compromise between measurement reliability, applicability, simplicity, and the necessity for repeated sampling in space and time. We also counted the number of shade trees, the canopy cover, vegetation height, soil cover, diameter at breast height, and total number of shade trees. Our findings contend that CN had the highest Ks values, indicating that shade trees have a positive impact on soil hydrological properties in shade-grown coffee agroecosystems. Additionally, CP had the highest VWC content and the greatest effect of leaf litter on soil temperature, indicating a positive impact of leaf litter on microclimatic conditions and soil moisture after seven years of agroforestry coffee plantation. The visual soil assessment suggested that CN had the highest score followed by CP, corroborating the results for Ks and VWC. The selected methodologies proved to be low cost and easy to implement. To counter shortcomings of these methodologies, we recommend monitoring infiltration in tropical land-use systems at regular intervals to better understand the temporal variability of infiltration recovery and ensure robust data in time and space.